Exposure to methamphetamine exacerbates motor activities and alters circular RNA profile of cerebellum - Mahdi Eskandarian Boroujeni; Amin Nasrollahi; Puria Baghbani Boroujeni; Fatemeh Fadaeifathabadi; Mohammaderfan Farhadieh; Ava Modirzadeh Tehrani; Hosein Nakhaei; Amir Masoud Sajedian; Tahmineh Peirouvi; Abbas Aliaghaei (Elsevier, 2020)
Methamphetamine (METH) is a psychostimulant drug that acts on monoaminergic systems in the brain. There are several lines of evidence indicating the devastating effects of addictive drugs on the cerebellum. Moreover, it was shown that circular RNAs (circRNAs) have an important role in neurodegenerative disorders. Herein, we explored the effects of METH on neuronal degeneration, motor coordination and muscle activity. We also inspected METH-mediated changes in circRNA expression profiling in the cerebellum. Accordingly, exposure to METH triggered destructive effects on the coordination of movement of rats along with disturbed muscle activity. The fluorescent staining exhibited a significant increase in neurodegeneration in the cerebellum under the influence of METH. Besides, the number of calbindin positive Purkinje cells noticeably declined in METH-treated group compared with the control. In this regard, we identified and characterized differentially expressed (DE) circRNAs in the cerebellum under METH treatment, mainly located in dendritic spines. Moreover, based on feature and function analyzes of host genes of DE circRNAs, a large number of these genes were essentially involved in cell growth, death, inflammation and oxidative metabolism. Taken together, this data might imply the potential involvement of circRNAs in METH neurotoxicity as well as motor activity deficits.